ANALISIS LARANGAN RANGKAP JABATAN MENTERI YANG BERASAL DARI UNSUR PARTAI POLITIK DALAM SISTEM KETATANEGARAAN INDONESIA - Moh. Baris Siregar; Catur Wido Haruni; Surya Anoraga (Indonesia Law Reform Journal, 2021)
Nowadays, concurrent positions are a political phenomenon that is rife, especially for Ministers who are concurrently chairman of political parties. This condition can cause various kinds of problems. As a result of multiple positions, issues arise, such as being vulnerable to conflicts of interest and power abuse. The purpose of this research is to know the regulation of concurrent ministerial positions from political party elements based on Article 23 of the State Ministry Law, to understand the legal implications of regulating simultaneous ministerial positions from political party elements based on Article 23 of the State Ministry Law, and to know the concept of setting the ideal clerical position in the future. The author's research method in examining this matter is the normative juridical approach, the statute approach method (Statue Approach), and the conceptual approach (Conceptual Approach). Juridically, the prohibition of concurrent ministerial positions is regulated in article 23 of Law Number 39 of 2008 concerning State Ministries. However, this article does not explicitly restrict the ban on current positions for the chairman of a political party who is also a minister. Because the alternative in dealing with concurrent ministerial positions is taken from the general chairperson of a political party, in the recruitment of ministers, the meritocracy system or the cabinet zaken system can obtain a minister following technical and professional specifications. Then the government can revise the State Ministry Law to get an ideal form of regulating the prohibition of concurrent ministerial positions in the future.